Optimalisasi Pencahayaan Alami di Pasar Batu Raja, Kec.Wasilei, Kabupaten Halmahera Timur - Utdin Furqon Amali; Sherly Asriany; Mohamad Jamil (Jurnal Teknik dan Science, 2025)
Batu Raja Market is in UPT. Subaim SP.2. This market is located at 1°04'38"N and 128°07'59"E. This market only operates once a week, namely on Saturdays around 06.00 WIT to 13.00 WIT. The market initially took the form of non-permanent trading stalls with tin roofs, cloth, plastic, tarpaulin and so on. In 2019 this market was built into a permanent market with a tin roof. This is where the problem comes from, if the market is built with a tin roof then the traders in the middle of the market will not get enough sunlight to carry out their activities. This research attempts to solve this problem by optimizing the entry of natural light into the market. The research method was carried out by making 2 (two) 1:1 scale models of Batu Raja Market using the Revit 2018 program. The first model of Batu Raja Market had a tin roof and the second model of Batu Raja Market had a skylight roof. Lighting simulations were carried out for both models using the DIALux 4.7 program. Research results show that markets with skylight roofs receive more sunlight than those with tin roofs, so that the market interior is brighter, flatter and visually pleasing (M.C. and Lam, 1986) and attracts the attention of buyers (Mark S. Rea, Ph. D., 1986).